Evaluation of the dose calculation accuracy for small fields defined by jaw or MLC for AAA and Acuros XB algorithms. Issue 10 (27th September 2016) - Fogliata, Antonella; Lobefalo, Francesca; Reggiori, Giacomo; Stravato, Antonella; Tomatis, Stefano; Scorsetti, Marta; Cozzi, Luca
Abstract : Purpose: Small field measurements are challenging, due to the physical characteristics coming from the lack of charged particle equilibrium, the partial occlusion of the finite radiation source, and to the detector response. These characteristics can be modeled in the dose calculations in the treatment planning systems. Aim of the present work is to evaluate the MU calculation accuracy for small fields, defined by jaw or MLC, for anisotropic analytical algorithm (AAA) and Acuros XB algorithms, relative to output measurements on the beam central axis. Methods: Single point output factor measurement was acquired with a PTW microDiamond detector for 6 MV, 6 and 10 MV unflattened beams generated by a Varian TrueBeam STx equipped with high definition‐MLC. Fields defined by jaw or MLC apertures were set; jaw‐defined: 0.6 × 0.6, 0.8 × 0.8, 1 × 1, 2 × 2, 3 × 3, 4 × 4, 5 × 5, and 10 × 10 cm 2 ; MLC‐defined: 0.5 × 0.5 cm 2 to the maximum field defined by the jaw, with 0.5 cm stepping, and jaws set to: 2 × 2, 3 × 3, 4 × 4, 5 × 5, and 10 × 10 cm 2 . MU calculation was obtained with 1 mm grid in a virtual water phantom for the same fields, for AAA and Acuros algorithms implemented in the Varianeclipse treatment planning system (version 13.6). Configuration parameters as the effective spot size (ESS) and the dosimetric leaf gap (DLG) were varied to find the best parameter setting. Differences between calculated and measured doses were analyzed. Results: Agreement better than 0.5% was found for field sizes equal to or larger than 2 × 2 cm 2 for both algorithms. A dose overestimation was present for smaller jaw‐defined fields, with the best agreement, averaged over all the energies, of 1.6% and 4.6% for a 1 × 1 cm 2 field calculated by AAA and Acuros, respectively, for a configuration with ESS = 1 mm for both X and Y directions for AAA, and ESS = 1.5 and 0 mm for X and Y directions for Acuros. Conversely, a calculated dose underestimation was found for small MLC‐defined fields, with the best agreement averaged over all the energies, of −3.9% and 0.2% for a 1 × 1 cm 2 field calculated by AAA and Acuros, respectively, for a configuration with ESS = 0 mm for both directions and both algorithms. Conclusions: For optimal setting applied in the algorithm configuration phase, the agreement of Acuros calculations with measurements could achieve the 3% for MLC‐defined fields as small as 0.5 × 0.5 cm 2 . Similar agreement was found for AAA for fields as small as 1 × 1 cm 2 .